The Predictive Value of Serum Progesterone and Estrogen Recepters as Diagnostic Tool for Premature Ovarian Failure (Medico Legal Update, 2021)
Background: Premature ovarian insufficiency (POI) is a delicate medical problem in young women. Thiscondition is not unchangeable and permanent but is associated with intermittent and unpredictable ovarianactivity, resulting in low conception rate. Over the period of 8 years, the evaluation of secondary amenorrheawas conducted in 90 patients below the age of 40 who wished to restore fertility and is characterized byirregular or absent periods and reduced fertility. Symptoms include those associated with the naturalmenopause (night sweats and vaginal dryness), and with the long-term adverse effects of estrogen deficiency(osteoporosis and cardiovascular disease): The latter is believed to explain the shorter life expectancyassociated with POI.Aim: To illustrate the predictive value of progesterone receptors (PRs), estrogen receptors (ERs), progesterone(PRG), estradiol (E2), Lulilizing hormones (LH), Follicle stimulating hormones (FSH) and Anti mullerianhormones (AMH) serum levels as diagnostic approach for POI.Method: Sixty (60) women with idiopathic POF with thirty (30) women as control groups were includedin the study. Baseline investigation in all subjects included serum progesterone receptors(PRs), estrogenreceptors(ERs), progesterone (PRG), estradiol (E2), Lulilizing hormones (LH), Follicle stimulatinghormones (FSH) and Anti mullerian hormones (AMH) levels were estimated using appropriate assays inbiochemistry laboratory.Results: There was statistically significant differences in the serum progesterone receptors, estrogenreceptors, progesterone, estradiol, LH, FSH and AMH in POI cases when compared with healthy control(P=